Reconstructing Zakat Management Through Political Culture: Insights from Madura - Dikuraisyin, Basar; Najah, Ahmadun (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
The gap between the potential of zakat funds and the reality of zakat collection is caused by the lack of trust and awareness among the community. This research aims to provide a solution through cultural reconstruction in zakat execution. This reconstruction is called cultural politicization, which combines social theory and legal institutions. Furthermore, this reconstruction generates an ideal organizational relationship proposal for zakat management institutions and reduces social non-compliance. By conducting in-depth interviews with zakat institutions (BAZNAS and LAZIZNU) in Sumenep Regency, Madura, using a qualitative-phenomenological approach, this research is based on legal sociology focusing on zakat culture and institutional relations. This research yields findings, namely the cultural construction in zakat law implementation consists of three aspects; 1) authority construction, where zakat collectors ranging from BAZNAS, LAZ to individual collectors (kiai, ulama, ustad) compromise the roles, with kiai and ulama as zakat collectors and BAZNAS as partners. 2) personal community construction, making the community as the subject of empowerment for productive fund programs and supportive stakeholders. 3) literacy-stigmatization construction, where the community is made as members of partner organizations of zakat collectors. Another finding is that the development of zakat management organization (OPZ) relations involves making BAZNAS, LAZ, and individual collectors as business partners who cooperate. This study also implies that BAZNAS acts as a regulator and formulator of productive zakat programs, while LAZ and individual collectors act as operators who carry out zakat management functions from collection to distribution and implement productive zakat utilization programs.